A figurational viewpoint of the complexity of policy enactment: An opportunity for agonistic dialogue?. Issue 2 (15th September 2022) - Scanlon, Dylan; MacPhail, Ann; Calderón, Antonio
Abstract: The aim of this paper is to explore and provide an alternative theoretical viewpoint, informed by empirical studies, of the curriculum policy enactment process which spans across different curriculum policy spaces by drawing on figurational sociology. This paper constructs this alternative figurational viewpoint of the policy enactment process by drawing on curriculum policy and policy enactment literature. This viewpoint highlights how a curriculum policy can be (re‐)interpreted, (re‐)translated and (re‐)enacted by multiple, interconnected and interdependent (face‐to‐face and non‐face‐to‐face, recognised and unrecognised, past and present) relationships. We argue the need for agonistic dialogue between the stakeholders of the educational community and how his could lead to these stakeholders working together across curriculum policy spaces (e.g., curriculum development, teacher education, professional development) and on different aspects of 'doing' policy work. We encourage ourselves, and colleagues, to advocate for, support and provide evidence on the centrality of construction and enactment of curriculum policy in effective curriculum change.